2009
DOI: 10.1177/0022034509355919
|View full text |Cite
|
Sign up to set email alerts
|

Resin-modified Glass-ionomer Setting Reaction Competition

Abstract: Resin-modified glass ionomers (RMGI) set by at least 2 mechanisms dependent upon reactant diffusion prior to gelation. Each reaction's kinetics and setting mechanism may rely on and/or compete with the other. In this study, we investigated RMGI setting reaction interactions using differential scanning calorimetry (DSC) by varying light-cure initiation times. A RMGI was analyzed with isothermal and dynamic temperature scan DSC with light-curing occurring immediately, or at 5 or 10 minutes after mixing as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
97
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 35 publications
1
97
1
4
Order By: Relevance
“…in attempt to improve mechanical properties, decrease setting time, and reduce moisture sensitivity of glass ionomer materials. 2,3,4 Hybrid ionomer were used for restorations on low-stressbearing areas and recommended for patients with high risk caries more esthetic than glass ionomers due to the resin content. 2,5,6 Hybrid ionomer setting reactions were by the acid base reaction between Fluro aluminosilicate glass powder and acid liquid and polymerization reaction with chemical activator or beam.…”
Section: Introductionmentioning
confidence: 99%
“…in attempt to improve mechanical properties, decrease setting time, and reduce moisture sensitivity of glass ionomer materials. 2,3,4 Hybrid ionomer were used for restorations on low-stressbearing areas and recommended for patients with high risk caries more esthetic than glass ionomers due to the resin content. 2,5,6 Hybrid ionomer setting reactions were by the acid base reaction between Fluro aluminosilicate glass powder and acid liquid and polymerization reaction with chemical activator or beam.…”
Section: Introductionmentioning
confidence: 99%
“…Los ionómeros de vidrio resino modificados constituyen uno de los últimos materiales incorporados como bases intermedias, los cuales fueron introducidos en el mercado entre los años 1993 y 1994, pudiendo ser utilizados como materiales de restauración definitiva. Su composición, compatibilidad bioló-gica y acción adhesiva a la dentina y al esmalte son muy similares a los ionómeros convencionales [18]. Sus mejores propiedades mecánicas le permiten ser grabado [16][17][18][19].…”
Section: Introductionunclassified
“…Su composición, compatibilidad bioló-gica y acción adhesiva a la dentina y al esmalte son muy similares a los ionómeros convencionales [18]. Sus mejores propiedades mecánicas le permiten ser grabado [16][17][18][19]. La sensibilidad a corto plazo por el agua resulta del ablandamiento de la superficie y, como consecuencia, una baja resistencia al desgaste, lo que limita el potencial del cemento ionómero de vidrio para las aplicaciones dentales [13].…”
Section: Introductionunclassified
“…RMGIs contain components of glass ionomers (fluoro-aluminosilicate glasses and polyacrylic acid) as well as resin composites (photo or chemical initiators and methacrylate monomers). 10 Due to their hybrid nature, RMGIs bond to dentin through both an ionic bond between polyacrylic acid and hydroxyapatite and mechanical interlocking with collagen and the resin monomer. 11 The initiation of this bond can be attributed to the various methods of polymerization of the RMGIs.…”
Section: Introductionmentioning
confidence: 99%
“…12 Recent studies have shown the acid-base and photo-initiated free-radical reactions inhibit each other, with photopolymerization of RMGIs reducing the acid-base reaction. 10,13 Another recent study concluded that the acid-base induced chemical interaction between RMGI and dentin is the main mechanism of bonding with RMGI. 14 Therefore, it is hypothesized that RMGIs allowed to polymerize without light activation will develop bond strength through the ionic bonding between RMGIs and dentin and should therefore have an equivalent or higher bond strength than light-cured RMGIs.…”
Section: Introductionmentioning
confidence: 99%